Optimization of Sulfurization Process of Cobalt Sulfide and Nitrogen Doped Carbon Material for Boosting the Oxygen Reduction Reaction Catalytic Activity in Alkaline Medium - Song, Bing-Ye; Yao, Sen (Frontiers in Chemistry, 2020)
In order to reduce fuel cell material cost and promote the application, it is urgent to develop non-noble metal materials to replace platinum as the cathode catalysts in fuel cells. The cobalt sulfide and nitrogen co-doped carbon (S-Co-N/C) materials with metal-organic frameworks as precursors have shown good oxygen reduction reaction (ORR) catalytic activity. Benefiting from the protection of catalytic active sites by sulfur atoms, the stability and alcohol-tolerance of the S-Co-N/C catalyst can be significantly improved. In order to fully understand the effect of the sulfurization process on the properties of the material, zeolite imidazole frameworks (ZIF)-8 and ZIF-67 are used as precursors to prepare a novel material of S-Co-N/C by using a sulfurization-pyrolysis method. Another S-Co-N/C material by using a pyrolysis- sulfurization method are prepared for comparison. The effects of the sulfurization process in the preparation on the morphology, chemical structure, specific surface area, and ORR catalytic activity of the final material are investigated. The experimental results show that the surface of the S-Co-N/C material tends to be roughness due to the sulfurization reaction of the metal elements. The porosity of the material is reduced to some extent due to the remained Zn elements in the final product. Interestingly, some carbon nanotubes are found to be generated on the surface of the S-Co-N/C material because of the synergistic effect of Zn and Co on the carbon material during the pyrolysis process, which is beneficial to accelerate the adsorption of oxygen on the S-Co-N/C surface and the electron transportation during the oxygen reduction reaction. In addition, the generated CoS during the sulfurization process can further protect the Co elements from agglomeration, which can effectively increase the ORR catalytic active sites in the final material. The S-Co-N/C material prepared by the sulfurization-pyrolysis method performs a superior ORR catalytic activity to the one synthesized by the pyrolysis-sulfurization method.